2004
DOI: 10.1590/s0104-66322004000300009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature and flow rate on the clarification of the aqueous stevia-extract in a fixed-bed column with zeolites

Abstract: -Stevia is being used as a sweetener due to its low calorific value and its taste, which is very similar to that of sucrose. After extraction from dried leaves, stevia extract is dark in colour so needs to be clarified for better acceptance by consumers. Adsorption is one of the most important processes in this clarification. In this work the clarification of extract stevia extract in fixed-bed columns with calcium zeolites was studied. Two temperatures (10 º C and 30 º C) and six different flow rates (2, 5, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 9 publications
0
16
0
2
Order By: Relevance
“…lower than the 80% obtained by Moraes and Machado (2001) with CaX zeolite. Mantovaneli et al (2004) and Moraes and Machado (2001) observed that temperature had a negative effect on colour removal using zeolites. However, in the present work, temperature has been found to have a positive effect on colour removal using alginate beads.…”
Section: Colour Removal From the Aqueous Stevia Extractmentioning
confidence: 99%
See 4 more Smart Citations
“…lower than the 80% obtained by Moraes and Machado (2001) with CaX zeolite. Mantovaneli et al (2004) and Moraes and Machado (2001) observed that temperature had a negative effect on colour removal using zeolites. However, in the present work, temperature has been found to have a positive effect on colour removal using alginate beads.…”
Section: Colour Removal From the Aqueous Stevia Extractmentioning
confidence: 99%
“…According to Peretz and Cinteza (2008), the removal efficiency towards cationic molecules is strongly dependent on the pH value. With increasing pH, the charged sites on the surface of calcium alginate become more negative.…”
Section: Colour Removal From the Aqueous Stevia Extractmentioning
confidence: 99%
See 3 more Smart Citations